Hyaluronic Acid–Based Activatable Nanomaterials for Stimuli‐Responsive Imaging and Therapeutics: Beyond CD44‐Mediated Drug Delivery. Issue 34 (18th February 2019) - Choi, Ki Young; Han, Hwa Seung; Lee, Eun Sook; Shin, Jung Min; Almquist, Benjamin D.; Lee, Doo Sung; Park, Jae Hyung
Abstract: There is a rapidly increasing interest in developing stimuli‐responsive nanomaterials for treating a variety of diseases. By enabling the activation of function locally at the sites of interest, it is possible to increase therapeutic efficacy significantly while simultaneously reducing adverse side effects. While there are many sophisticated nanomaterials available, they are often highly complex and not easily transferrable to industrial scales and clinical settings. However, nanomaterials based on hyaluronic acid offer a compelling strategy for reducing their complexity while retaining several desirable benefits such as active targeting and stimuli‐responsive degradation. Herein, the basic properties of hyaluronic acid, its binding partners, and natural routes for degradation by hyaluronidases—hyaluronic‐acid‐degrading enzymes—and oxidative stresses are discussed. Recent advances in designing hyaluronic acid–based, actively targeted, hyaluronidase‐ or reactive‐oxygen‐species‐responsive nanomaterials for both diagnostic imaging and therapeutic delivery, which go beyond merely the classical targeting of CD44, are summarized. Abstract : Hyaluronic‐acid‐based nanomaterials offer compelling strategies not only for passive and active targeting but also for stimuli‐responsive imaging and therapeutics. Without additional hydrophilic stealth polymer and active targeting ligands, HA nanomaterials both passively and actively target tissues displaying overexpression of hyaladherins. Furthermore, the inherent degradability of HA gives rise to stimuli‐responsive activation of the desired functions spatially and temporally.